The economy in Jewish history : new perspectives on the interrelationship between ethnicity and economic life - Reuveni, Gideon; Wobick-Segev, Sarah (Berghahn Books, 2011)
Jewish historiography tends to stress the religious, cultural, and political aspects of the past. By contrast the economyA" has been pushed to the margins of the Jewish discourse and scholarship since the end of the Second World War. This volume takes a fresh look at Jews and the economy, arguing that a broader, cultural approach is needed...